2010
DOI: 10.1007/s11999-009-1090-5
|View full text |Cite
|
Sign up to set email alerts
|

Do Tantalum and Titanium Cups Show Similar Results in Revision Hip Arthroplasty?

Abstract: Porous surfaces are intended to enhance osteointegration of cementless implants. Tantalum has been introduced in an effort to enhance osseointegration potential of uncemented components. We therefore compared the clinical outcome of acetabular components with two different porous surfaces. We retrospectively reviewed 283 patients (295 hips) who underwent cementless revision hip arthroplasty with either an HA-coated titanium cup (207 patients, 214 hips) or porous tantalum cup (79 patients, 81 hips). The minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 26 publications
1
55
0
3
Order By: Relevance
“…These tantalum implants are clearly beneficial compared to previously used roof reinforcement rings and cages in the presence of a large acetabular defect [24,25].…”
Section: Discussionmentioning
confidence: 93%
“…These tantalum implants are clearly beneficial compared to previously used roof reinforcement rings and cages in the presence of a large acetabular defect [24,25].…”
Section: Discussionmentioning
confidence: 93%
“…The highly porous characteristics of these new porous metal compounds are claimed to further increase rapid and early osteointegration [22,34] and should therefore diminish the loosening rate and improve clinical results and long term outcomes. If failures occur, they tend to happen early on in the postoperative period according to Jafari et al [35]; in their group of 79 patients who had undergone total hip revision surgery with TM augments, 4 out of 5 failures occurred in the first 6 months postoperatively. However, the advantages of these porous implants are negated if they are cemented to viable bone.…”
Section: Discussionmentioning
confidence: 99%
“…The newer metals have high porosity and greater surface frictional properties which potentially can improve the initial fixation strength of the cup-bone interface and enhance osseointegration and durable long-term fixation. Jafari et al in a retrospective analysis of 295 hips at approximately twoto four-year follow-up reported that hips with major acetabular bone loss had lower aseptic failure rates with tantalum cups (12 %; three out of 26 hips) in comparison to conventional porous-coated cups (24 %; five out of 21 hips) [48]. The aseptic failure rate in the minor bone loss group using tantalum was 6 % (five out of 81) in comparison to 8 % (17 out of 214 hips) with conventional implants.…”
Section: Discussionmentioning
confidence: 99%